Respostas ecofisiológicas e bioquímicas ao déficit hídrico em Ziziphus joazeiro Mart. Em duas eco-regiões do Estado de Sergipe Agreste e Sertão - Santos, Lívia Maria de Jesus (2013)
This study had the objective to evaluate the ecophysiological responses of juazeiro (Ziziphus joazeiro Mart.) Under field conditions in two ecoregions of the state of Sergipe (Agreste and Sertão) in different seasons (wet and dry), with the aim of understand the survival strategies used by this species to the local climate. For this we evaluated: photosynthesis, stomatal conductance, transpiration, water potential of stem branches, the chlorophyll fluorescence, pigment levels and osmotic adjustment through the accumulation of organic solutes (carbohydrates, protein and proline). During the year 2012 the amount of precipitation was below average in the Sertão. The rate of photosynthesis (A) was higher in the ecoregion Agreste in the rainy season and lowest in the Sertão in the dry season. The stomatal conductance (gs) was higher during the hours that the vapor pressure deficit (VPD) was lower, keeping the rate of assimilation and avoiding excessive water loss through transpiration (E). The stem water potential (hydrotime) was higher during the wet season in the ecoregion Sertão and lower in the dry season, this time there was a greater accumulation of carbohydrates in leaves and chlorophyll index was lower. Regarding the chlorophyll fluorescence was found that individuals had rates within the normal range, indicating no stress condition, while in the dry Sertão there has been a decrease in the efficiency of photosystem II, where the index and performance area pool of electrons transported by the Calvin cycle were lower. Was conclude that this species presents efficient strategies for survival, maintaining its photosynthetic apparatus functioning even during dry periods under high temperatures and low relative humidity.